Lanostane-type C31 triterpenoid derivatives from the fruiting bodies of cultivated Fomitopsis palustris. (August 2018) - Zhao, Jinzhi; Yang, Yun; Yu, Mengyao; Yao, Ke; Luo, Xia; Qi, Huayi; Zhang, Guolin; Luo, Yinggang
Abstract: Fifteen undescribed and five known lanostane-type C31 triterpenoid derivatives were isolated from the aqueous EtOH extract of the fruiting bodies of cultivated Fomitopsis palustris. Their structures were identified from the spectroscopic data and chemical degradation studies. The structures of palustrisoic acids A and H were confirmed by X-ray crystallography. Polyporenic acid B showed strong cytotoxicity against the HCT116, A549, and HepG2 cell lines with IC50 values of 8.4, 12.1, and 12.2 μM, respectively. Palustrisolides A, C, and G displayed weak cytotoxicity. Graphical abstract: Image 1 Highlights: Twenty C31 triterpenoid derivatives were identified from Fomitopsis palustris. Palustrisoic acids A and H were confirmed by X-ray crystallography. Polyporenic acid B showed strong cytotoxicity. Palustrisolides A, C, and G displayed weak cytotoxicity.